Cloxacillin or fosfomycin plus daptomycin combinations are more active than cloxacillin monotherapy or combined with gentamicin against MSSA in a rabbit model of experimental endocarditis. (27th August 2020) - García-de-la-Mària, Cristina; Gasch, Oriol; Castañeda, Ximena; García-González, Javier; Soy, Dolors; Cañas, Maria-Alexandra; Ambrosioni, Juan; Almela, Manel; Pericàs, Juan M; Téllez, Adrián; Falces, Carlos; Hernández-Meneses, Marta; et al.
Abstract: Background: In vitro and in vivo activity of daptomycin alone or plus either cloxacillin or fosfomycin compared with cloxacillin alone and cloxacillin plus gentamicin were evaluated in a rabbit model of MSSA experimental endocarditis (EE). Methods: Five MSSA strains were used in the in vitro time–kill studies at standard (10 5 –10 6  cfu/mL) and high (10 8  cfu/mL) inocula. In the in vivo EE model, the following antibiotic combinations were evaluated: cloxacillin (2 g/4 h) alone or combined with gentamicin (1 mg/kg/8 h) or daptomycin (6 mg/kg once daily); and daptomycin (6 mg/kg/day) alone or combined with fosfomycin (2 g/6 h). Results: At standard and high inocula, daptomycin plus fosfomycin or cloxacillin were bactericidal against 4/5 and 5/5 strains, respectively, while cloxacillin plus gentamicin was bactericidal against 3/5 strains at standard inocula but against none at high inocula. Fosfomycin, cloxacillin, gentamicin and daptomycin MIC/MBCs of the MSSA-678 strain used in the EE model were: 8/64, 0.25/0.5, 0.25/0.5 and 1/8 mg/L, respectively. Adding gentamicin to cloxacillin significantly reduced bacterial density in vegetations compared with cloxacillin monotherapy ( P =  0.026). Adding fosfomycin or cloxacillin to daptomycin [10/11 (93%) and 8/11 (73%), respectively] significantly improved the efficacy of daptomycin in sterilizing vegetations [0/11 (0%), P <  0.001 for both combinations] and showed better activity than cloxacillin alone [0/10 (0%), P <  0.001 for both combinations] and cloxacillin plus gentamicin [3/10 (30%), P =  0.086 for cloxacillin plus daptomycin and P =  0.008 for fosfomycin plus daptomycin]. No recovered isolates showed increased daptomycin MIC. Conclusions: The addition of cloxacillin or fosfomycin to daptomycin is synergistic and rapidly bactericidal, showing better activity than cloxacillin plus gentamicin for treating MSSA EE, supporting their clinical use.